Advances in minimally invasive surgical techniques for lumbar disc herniation: a comprehensive review - Lan, Weiqiang; Cui, Hanbing; Zhou, Di; Xiao, Xiao; Xiong, Hongbo (Frontiers in Surgery, 2025)
Lumbar disc herniation (LDH) is a common and frequent disease in orthopaedics, which seriously affects patients’ physical and mental health as well as their daily life and work. There are various treatment methods for this condition, and different treatment plans should be adopted according to different situations. Traditional open surgery methods are relatively traumatic and have longer recovery times, while minimally invasive spine techniques have advantages such as smaller incisions, less bleeding, higher fusion rates, and faster recovery. This review summarizes the relevant literature on the application of minimally invasive techniques in the treatment of lumbar disc herniation in recent years, analyzes and compares the advantages and disadvantages of different approaches and endoscopic techniques, as well as reduction, decompression, and fusion effects. The aim is to provide reference for surgeons in selecting surgical procedures for the treatment of LDH.